2015
DOI: 10.1371/journal.pone.0144096
|View full text |Cite
|
Sign up to set email alerts
|

Associated Liver Partition and Portal Vein Ligation (ALPPS) vs Selective Portal Vein Ligation (PVL) for Staged Hepatectomy in a Rat Model. Similar Regenerative Response?

Abstract: Associated liver partition and portal vein ligation for staged hepatectomy (ALPPS) is a two-stage hepatectomy technique which can be associated with a hypertrophic stimulus on the future liver remnant (FLR) stronger than other techniques–such as portal vein ligation (PVL). However, the reason of such hypertrophy is still unclear, but it is suggested that liver transection combined with portal vein ligation (ALPPS) during the first stage of this technique may play a key role. The aim of this study is to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 45 publications
(59 reference statements)
6
55
0
Order By: Relevance
“…Our data revealed that time-dependent factors appear to be the major source of variation in post-injury alterations of gene expression in liver regeneration. Early transcriptomic changes and the upstream regulators after all the procedures included cell cycle associated genes (E2F1, CCND1, FOXM1, TP53, and RB1), transcription factors (Myc, E2F1, TBX2, FOXM1) [23][24][25][26][27][28] , DNA replication regulators (CDKN1A, EZH2, RRM2) 29 , G1/S-transition regulators (CCNB1, CCND1, RABL6) 30 , cytokines and growth factors (CSF2, IL-6, TNF, HGF, VEGF, and EGF) 9,16,31,32 . At the cellular level, this corresponds to the transition from the quiescent G0 phase to active mitosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data revealed that time-dependent factors appear to be the major source of variation in post-injury alterations of gene expression in liver regeneration. Early transcriptomic changes and the upstream regulators after all the procedures included cell cycle associated genes (E2F1, CCND1, FOXM1, TP53, and RB1), transcription factors (Myc, E2F1, TBX2, FOXM1) [23][24][25][26][27][28] , DNA replication regulators (CDKN1A, EZH2, RRM2) 29 , G1/S-transition regulators (CCNB1, CCND1, RABL6) 30 , cytokines and growth factors (CSF2, IL-6, TNF, HGF, VEGF, and EGF) 9,16,31,32 . At the cellular level, this corresponds to the transition from the quiescent G0 phase to active mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, this corresponds to the transition from the quiescent G0 phase to active mitosis. Liver regeneration is governed by numerous growth factors, including HGF and EGF that are responsible priming the parenchymal and nonparenchymal liver cells and boosting their access into the cell cycle to proliferate to restore the original liver size after the surgical procedures 9,16,31,32 . Growth factors and signaling pathways activates cyclin-dependent kinases (CDKs), and upregulates the expression of CCND1 that encodes cyclin D1.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6, TNF-a, EGF and HGF are critical promoters of liver regeneration 37 and have also been described in animal models of ALPPS. 38 These cytokines and growth factors were increased in serum from patients before ALPPS Stage II.…”
Section: Discussionmentioning
confidence: 92%
“…At 48h, ALPPS was associated with higher expression of HGF and TGF-α ( P < 0.05) with similar relative expression of TGF-β in both groups[59]. Later, the HGF and TGF-β levels were still higher on ALPPS group ( P < 0.005 and P < 0.05 respectively)[59].…”
Section: Resultsmentioning
confidence: 99%